Benefits and Risks of Mammography Screening in Women Ages 40 to 49 Years - Lars J. Grimm; Carolyn S. Avery; Edward Hendrick; Jay A. Baker (SAGE Publishing, 2022)
Breast cancer screening in the United States is complicated by conflicting recommendations from professional and governmental organizations. The benefits and risks of breast cancer screening differ though by age which should influence shared decision-making discussions. Compared to older women, women ages 40 to 49 years have a lower risk of breast cancer, but the types of breast cancer that develop are often more aggressive with a poorer prognosis. Furthermore, younger women have a longer life expectancy and fewer comorbidities. The primary benefits of screening for women in their 40s are a reduction in breast cancer mortality, years of life lost to breast cancer, and morbidity of breast cancer treatment by detecting cancers at an earlier stage. Compared to older women, the risks of breast cancer screening in women ages 40 to 49 years includes more false positive recalls and biopsies as well as transient anxiety. Concerns regarding radiation induced malignancy and overdiagnosis are minimal in this age group. The shorter lead time of breast cancer in women ages 40 to 49 years also favors shorter screening intervals. This information should help inform providers in their shared decision-making discussions with patients.